Practicing Islamic-Based Leadership: Arab Principals' Perspectives - Sawalhi, Rania; AlSaleh, Amal; Khulief, Jameelah (International Journal of Asian Education, 2024)
Although the literature offers various frameworks related to Islamic-based leadership, we argue that these frameworks have not fully encompassed all the preparations that Muslims must undertake for the afterlife. Al-Kaylani (1937–2015) is one of the Islamic philosophers who developed a relational model that connects individuals with the Creator, the universe, fellow human beings, life, and the afterlife. This qualitative study aims to explore the perspectives of Arab school leaders on the extent to which they apply Islamic-based leadership based on Al-Kaylani's relational model, as well as the factors influencing their practices. In this study, 13 school principals shared their perspectives and practices concerning what they refer to as Islamic schools and Islamic education within the Arab context. The findings reveal that the school leaders' understanding of Islamic education varies significantly based on their assumptions, influencing their practices and priorities in school planning and goals. Only one school leader attempted to align their practices with the afterlife. This study encourages researchers and practitioners to explore Al-Kaylani's model further and reimagine Islamic education's meaning in Muslim schools.